Tranexamic acid administration during liver transplantation is not associated with lower blood loss or with reduced utilization of red blood cell transfusion - Dehne, Sarah; Riede, Carlo; Feißt, Manuel; Klotz, Rosa; Etheredge, Melanie; Hölle, Tobias; Merle, Uta; Mehrabi, Arianeb; Michalski, Christoph; Büchler, Markus W.; Weigand, Markus A.; Larmann, Jan (Anesthesia & analgesia, 2024)
BACKGROUND: - Current clinical guidelines recommend antifibrinolytic treatment for liver transplantation to reduce blood loss and transfusion utilization. However, the clinical relevance of fibrinolysis during liver transplantation is questionable, a benefit of tranexamic acid (TXA) in this context is not supported by sufficient evidence, and adverse effects are also conceivable. Therefore, we tested the hypothesis that use of TXA is associated with reduced blood loss. - METHODS: - We performed a retrospective cohort study on patients who underwent liver transplantation between 2004 and 2017 at Heidelberg University Hospital, Heidelberg, Germany. Univariable and multivariable linear regression analyses were used to determine the association between TXA administration and the primary end point intraoperative blood loss and the secondary end point intra- and postoperative red blood cell (RBC) transfusions. For further secondary outcome analyses, the time to the first occurrence of a composite end point of hepatic artery thrombosis, portal vein thrombosis, and thrombosis of the inferior vena cava were analyzed using a univariable and multivariable Cox proportional hazards model. - RESULTS: - Data from 779 transplantations were included in the final analysis. The median intraoperative blood loss was 3000 mL (1600-5500 mL). Intraoperative TXA administration occurred in 262 patients (33.6%) with an average dose of 1.4 ± 0.7 g and was not associated with intraoperative blood loss (regression coefficient B, −0.020 [−0.051 to 0.012], P = .226) or any of the secondary end points (intraoperative RBC transfusion; regression coefficient B, 0.023 [−0.006 to 0.053], P = .116), postoperative RBC transfusion (regression coefficient B, 0.007 [−0.032 to 0.046], P = .717), and occurrence of thrombosis (hazard ratio [HR], 1.110 [0.903-1.365], P = .321). - CONCLUSIONS: - Our data do not support the use of TXA during liver transplantation. Physicians should exercise caution and consider individual factors when deciding whether or not to administer TXA.